2017
DOI: 10.1097/qai.0000000000001231
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Elevated Red Cell Distribution Width Identifies Elevated Cardiovascular Disease Risk in Patients With HIV Infection

Abstract: Red cell distribution width (RDW) is linked to cardiovascular risk in the general population, an association that might be driven by inflammation. Whether this relationship holds for patients with Human Immunodeficiency Virus (HIV) infection has not been previously studied. Using a large clinical registry, we show that elevated RDW (>14.5%) is independently associated with increased risk of coronary artery disease (odds ratio (OR) 1.39 [1.25–1.55]), peripheral vascular disease (OR 1.41 [1.29–1.53]), myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
(31 reference statements)
1
9
1
Order By: Relevance
“…47,48,49,50 Multiple groups, including our own, have identified relatively strong associations between RDW and clinical outcomes in a variety of populations. 51,52,53 An elevated RDW may reflect chronic inflammation, ultimately leading to altered iron homeostasis and erythropoietin resistence. 54,55 Associations between RDW and interleukin 6 have been demonstrated in heart failure 56 and in participants with human immunodeficiency virus infection, 57 and RDW was associated with tumor necrosis factor in those with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…47,48,49,50 Multiple groups, including our own, have identified relatively strong associations between RDW and clinical outcomes in a variety of populations. 51,52,53 An elevated RDW may reflect chronic inflammation, ultimately leading to altered iron homeostasis and erythropoietin resistence. 54,55 Associations between RDW and interleukin 6 have been demonstrated in heart failure 56 and in participants with human immunodeficiency virus infection, 57 and RDW was associated with tumor necrosis factor in those with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Kindi et al[40] used a large commercial database including electronic health records of many participating hospitals, with the aim of identifying patients aged 18 years or older with a diagnosis of HIV and who had at least one available RDW measurement. The search allowed the extraction of a total number of 46720 records (mean or median follow-up period for development of cardiovascular complications is unavailable in the article).…”
Section: Description Of Studies Outcomementioning
confidence: 99%
“…It has been postulated that increased RDW may reflect ineffective erythropoiesis that results from inflammation, oxidative stress, bone marrow failure, or nutritional deficiencies. Cross-sectional studies have shown that RDW correlates with markers of inflammation (eg TNF alpha, IL-6, and C-reactive protein) [6, 13, 14] in HIV-uninfected cohorts. To our knowledge, the association between RDW and immune activation in HIV has not been studied before.…”
Section: Introductionmentioning
confidence: 99%